2023
DOI: 10.3390/w15061021
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Rainfall Event Classification Using Machine Learning for Kikuletwa River Floods

Abstract: Advancements in machine learning techniques, availability of more data sets, and increased computing power have enabled a significant growth in a number of research areas. Predicting, detecting, and classifying complex events in earth systems which by nature are difficult to model is one such area. In this work, we investigate the application of different machine learning techniques for detecting and classifying extreme rainfall events in a sub-catchment within the Pangani River Basin, found in Northern Tanzan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…Technological progress has shifted towards machine learning (ML) and deep learning (DL), and recent studies have employed these algorithms to accurately derive GW-PZs [10,26,27] and improve model accuracy and efficiency [28]. The ML and DL techniques rely heavily on the availability and quality of the dataset [29] since these techniques learn from experience and identify hidden patterns [30]. Researchers have demonstrated the efficiency of ML and DL algorithms in various applications including landslide susceptibility mapping, floods, and groundwater prediction [6].…”
Section: Introductionmentioning
confidence: 99%
“…Technological progress has shifted towards machine learning (ML) and deep learning (DL), and recent studies have employed these algorithms to accurately derive GW-PZs [10,26,27] and improve model accuracy and efficiency [28]. The ML and DL techniques rely heavily on the availability and quality of the dataset [29] since these techniques learn from experience and identify hidden patterns [30]. Researchers have demonstrated the efficiency of ML and DL algorithms in various applications including landslide susceptibility mapping, floods, and groundwater prediction [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, the use of machine learning (ML) has received more attention in the field of water resource management around the world, including ET 0 estimation. ML has been applied to estimate the parameters of hydrology [39][40][41][42][43][44][45], hydraulics [46][47][48][49], and water quality by many researchers [42,[50][51][52][53]. Several previous studies have reported the capability of ML techniques in estimating ET 0 [54].…”
Section: Introductionmentioning
confidence: 99%